The comparative efficacy and safety of atorvastatin versus pravastatin in dyslipidemic patients on peritoneal dialysis - (:unkn) unknown (My University, 2003)
Objective: The aim of our study was to compare the efficacy and safety of atorvastatin versus pravastatin, in dyslipidemic patients on continuous ambulatory peritoneal dialysis (CAPD). Material and methods: Fifty-five hyperlipidemic CAPD patients were randomized to either atorvastatin (n=27) or pravastatin (n=28) treatment and prospectively followed for nine months. Hyperlipidemia was defined as TC ≥200mg/dl (5.2 mmol/L) and LDL-C ≥135 mg/dl (3.5 mmol/L). Both drugs were initiated at a dose of 10 mg/day and the doses were increased if LDL-C was >135 mg/dl at visits done every three months. The blood glucose, serum albumin total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), very low-density lipoprotein cholesterol (VLDL-C), triglyceride (TG), AST, ALT, GGT, uric acid, CPK, HbA1C were measured in the fasting blood samples taken at baseline, and at 3rd, 6th and 9th months of the treatment. Results: Both agents resulted in a marked reduction in the TC, LDL-C and TG levels; but no change was observed for VLDL-C and HDL-C in either of the treatment arms. The proportional decrease of TC and LDL-C was more marked in the atorvastatin group, compared to pravastatin group. No major side effects were observed with either of the statins in these patient groups. Conclusion: The results of our study demonstrated that although both statins improved the lipid profiles and both are safe for use in dyslipidemic CAPD patients, and higher starting doses (20 mg) may be required for pravastatin in patients on CAPD treatment.
Keywords: Atorvastatin; Continuous ambulatory peritoneal dialysis (CAPD); Dyslipidemia; Pravastatin